A novel hypocrellin-based assembly for sonodynamic therapy against glioblastoma. Issue 1 (29th November 2021) - Zhang, Chuangli; Wu, Jiasheng; Liu, Weimin; Zheng, Xiuli; Zhang, Wenjun; Lee, Chun-Sing; Wang, Pengfei
Abstract : A cysteamine and tryptophan-modified hypocrellin derivative was synthesized and a novel hypocrellin-based assembly was prepared. This assembly could be used as an effective sonosensitizer for sonodynamic therapy against glioblastoma. Abstract : The non-invasive treatment of glioblastoma (GBM) is of great significance and can greatly reduce the complications of craniotomy. Sonodynamic therapy (SDT) is an emerging tumor therapeutic strategy that overcomes some fatal flaws of photodynamic therapy (PDT). Different from PDT, SDT has deep tissue penetration and can be applied in the non-invasive treatment of deep-seated tumors. However, effective sonosensitizers that can be used for SDT of GBM are still very rare. Herein, we have prepared a suitable assembly based on a hypocrellin derivative (CTHB ) with good biocompatibility. Excitedly, the hypocrellin-based assembly (CTHB NPs ) can effectively produce reactive oxygen species under ultrasound stimulation. The inherent fluorescence and photoacoustic imaging characteristics of the CTHB NPs are conducive to the precise positioning of the tumors. It has been proved both in subcutaneous and in intracranial tumor models that CTHB NPs can be used as an effective sonosensitizer to inhibit tumor growth under ultrasound irradiation. This hypocrellin-based assembly has a good clinical prospect in the non-invasive treatment of GBM.